The Relevance of Financial Services Authority Policy Direction on Fintech Lending in Realising Sustainable Development Goals - Nancy Silvana Haliwela; Sunarno Sunarno; Ahmad Masum (PROGRAM STUDI MAGISTER HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO, 2025)
Sustainable Development Goals (SDGs) in the economic sector cover various aspects, including poverty-oriented economic development. The financial sector has undergone modernisation marked by the emergence of financial technology (fintech). In Indonesia, fintech is regulated by Financial Services Authority Regulation (POJK) No. 40 of 2024, but this regulation has weaknesses. This study aims to identify the relevance between SDG principles and current fintech practices and to formulate the direction of POJK No. 40 of 2024 on fintech lending in realising SDGs in Indonesia. The research method used is normative juridical based on literature, referring to laws and regulations, books, journals, and supporting data. The analysis was conducted descriptively through a legal and conceptual approach. The results of the study indicate that fintech lending has a strong connection with the SDGs pillars, so fintech policies need to be directed in line with the vision of sustainable development. The regulations in POJK No. 40 of 2024 have the potential to hinder the establishment of business entities and trigger the emergence of illegal services. Therefore, a balance of policies and increased socialisation are needed to improve the legal culture of society.